23 Timing of concentrate supplementation during late gestation impacts calf pre-weaning growth, but not reproductive performance of Bos indicus-influenced cows. (29th July 2019) - Palmer, Elizabeth; Vedovatto, Marcelo; Ranches, Juliana; Miranda, Miguel; Gouvêa, Vinícius; Arthington, John; Vendramini, João; Moriel, Philipe
Abstract: This study evaluated the effects of timing of dried distillers grains (DDG) supplementation during late-gestation on performance of Bos indicus-influenced cow-calf pairs. At about 84 d before calving (d 0), 84 mature Brangus cows were stratified by BW and BCS (422 ±42 kg; BCS = 5.0 ± 0.14) and assigned randomly to bahiagrass pastures (14 cows/pasture). Treatments were assigned randomly to pastures (2 pastures/treatment) and consisted of no prepartum supplementation (CON), 1 kg/d of DDG from d 0 to 84 (LATE84; 84 kg of DM/cow); or 2 kg/d of DDG from d 0 to 42 (LATE42; 84 kg of DM/cow). The respective weekly supplement amount was divided and offered into 3 feeding events (Monday, Wednesday, and Friday). Cow BCS were assessed on d 0, 45, 84 (calving), 140 and 224 (start and end of breeding season, respectively). Calf BW was collected at birth and weaning (d 346). Growth and reproductive data were analyzed using SAS MIXED and GLIMMIX procedures, respectively. Cow BCS from d 45 to 224 did not differ between LATE84 and LATE42 cows (P ≥ 0.20) but was always the least (P ≤ 0.05) for CON cows. Calving date, calf birth BW, and percentage of pregnant cows on d 283 did not differ (P ≥ 0.19) among treatments. Calf pre-weaning ADG and BW at weaning did not differ (P ≥ 0.58) between LATE42 and CON calves, but LATE84 calves tended to have the greatest pre-weaning ADG (P = 0.10; 0.88, 0.83, and 0.82 ± 0.02 kg/d, respectively) and BW at weaning (P = 0.10; 263, 254, and 252 ± 4.4 kg, respectively). Therefore, timing of prepartum DDG supplementation did not impact cow reproductive performance. However, calf pre-weaning growth tended to be enhanced when cows received longer vs. shorter or no periods of prepartum DDG supplementation